2022
DOI: 10.1123/jmld.2021-0066
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Bilateral Skill Symmetry: Insights From Gaelic Football Players and Coaches

Abstract: Developing players who are adept at using both sides of the body (i.e., bilateral skill) is a challenge for coaches in many sports. With players being required to execute a range of skills with hand and foot on both sides of the body, Gaelic football provides an ideal natural laboratory for the study of laterality. Previous quantitative research has produced equivocal findings regarding the importance of bilateral skill performance in sport. In light of this equivocality, this paper utilized a qualitative appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Given the rarity we uncovered with respect to close proximity of opponents in Gaelic football when executing three of the skills we analyzed, there is reason to question the importance of having the ability to use the non-dominant side for these three skills. Moreover, it is hard to use skill success as the determinant that a given choice was optimal, since non-dominant limb use, even if less successful on average, may have offered better tactical opportunities in a given game context ( Dillon et al, 2022 ). Thus, future research into bilateral skill should measure both the appropriateness of decision making and the effectiveness of skill execution ( Oslin et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the rarity we uncovered with respect to close proximity of opponents in Gaelic football when executing three of the skills we analyzed, there is reason to question the importance of having the ability to use the non-dominant side for these three skills. Moreover, it is hard to use skill success as the determinant that a given choice was optimal, since non-dominant limb use, even if less successful on average, may have offered better tactical opportunities in a given game context ( Dillon et al, 2022 ). Thus, future research into bilateral skill should measure both the appropriateness of decision making and the effectiveness of skill execution ( Oslin et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to perform skills bilaterality is widely believed to be a key characteristic of high-level sports performers because it increases the likelihood of players finding a solution for each scenario they face ( Dillon et al, 2022 ; Moore, O’Dwyer, et al, 2017 ; Parrington & Ball, 2015 ; Stöckel & Vater, 2014 ). There is some support for this position in that Murray et al (2023) found that bilateral Gaelic football players were more likely to be selected for a county under 17 team than their more unilateral counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation